(untitled) (Research, Society and Development, 2018)
The present work aims to analyze the political-philosophical reflection of Hannah Arendt who, in a tone of criticism of the solipsistic model of foundation that emerged in modernity and to affirm her thinking, confronts her by seeking the inspiration of the classical political tradition for her inspiration. Arendt brings to the surface the concept of Public Space as essential to establishing a true political experience. Methodologically based in the bibliographical analysis of works such as The Human Condition, this work brings fundamental elements to the reflection on education in face of the current challenges in the educational field. The being to assert itself in the political space is aided by word and action as an educational process and at the same time forging the public debate that constitutes the very foundation of the political life of the ’educated subjects’, in this sense, the current educational reform denies the school this space by removing the compulsory nature of disciplines such as Philosophy. The present study attempts to broaden the discourse about Philosophy in the school, without its aid the education of future generations, the ’new’ who come to the world by birth are compromised in their access to the common world. From the perspective of Arendtian thinking, looking back to its origins in the classical tradition and passing through the other forms of its approach with emphasis in education in the essay titled ’The crisis in education’ Arendt establishes the focus of this criticism. We conclude that the Arendtian reflection enables us to perceive elements that will help us to establish an analysis of the real obscurantist goals of the current reform that continues the sad history of intermittence in the Teaching of Philosophy in Brazilian education.